(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the national and cultural characteristics of non-verbal behavior, focusing on how gestures, facial expressions, eye contact, body language, and spatial distance differ across various cultures. It emphasizes the importance of understanding these differences in cross-cultural communication and highlights how non-verbal signals can carry different meanings depending on cultural context. The study shows that while non-verbal behavior is a universal part of human communication, its interpretation is deeply shaped by national traditions, social norms, and historical experience. Awareness of these features is crucial for avoiding misunderstandings and fostering mutual respect in international interactions.